MUSLIM MILLENNIAL’S INTENTION OF DONATING FOR CHARITY USING FINTECH PLATFORM - Farokhah Muzayinatun Niswah; Lu'liyatul Mutmainah; Diah Ayu Legowati (Journal of Islamic Monetary Economics and Finance, 2019)
Financial Technology (fintech) has been a part of human life. Fintech becomes a solution of human needs without limits of space and time. Fintech makes it easy for people especially millennials to make donation. This study aims to explore the factors that influence Muslim millennial’s intention in giving donation through fintech. This study uses an integration model of Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB). Online survey is used in this research including 115 Muslim millennials as sample. Data analized by Structural Equation Model (SEM) using Smart PLS. The results indicate that Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) have no significant effect on Attitude Towards Usage (ATU), Attitude Towards Usage (ATU) has no significant effect on Behavioral Intention (BI), Perceived Usefullness (PU), Subjective Norm (SN) and Perceived Behavioral Control (PBC) significantly have a positive effect on Behavioral Intention (BI). Overall fintech improves Muslim millennial’s intention to make donation easily and almost all of respondents know about fintech, even not all of the use fintech to donate. This research contributes both theoretically and practically.